Sistema cooperativo OFDMA UPLINK Multiusuário com amplificadores de potência não lineares: caracterização teórica e alocação de recursos - Magalhães, Syllas Rangel Carneiro (2020)
In this work, a multiuser and multirelay cooperative OFDMA uplink system with nonlinear power amplifiers in both users and relays is investigated, for both massive MIMO and singleantenna base station scenarios. Firstly, a theoretical characterization of the considered scenario is performed. Analytical expressions for the power amplifier nonlinear distortion variance derived in a previous work are generalized for the considered scenario. In addition, closed-form expressions for the instantaneous signal-to-noise ratio (SNR) of the considered system are derived. These developed expressions, in addition to providing a characterization of the link quality of the system, are used by the power allocation algorithms proposed in this dissertation. Then, two relay selection and subcarrier allocation techniques are proposed to solve the considered problem, both with the objective of maximizing the total system capacity. The first proposed technique is a heuristic algorithm with low computational complexity, developed based on the expressions for instantaneous SNR of the system. The second proposed technique is based on genetic algorithm, with the calculation of the individual’s fitness also based on the developed SNR expressions. Numerical simulation results validate the derived expressions and show that the proposed techniques provide considerable capacity gains in relation to the case where nonlinear distortions are not taken into account.